Pengaruh Biaya Pencegahan Dan Biaya Penilaian Terhadap Produk Cacat Digital Keyphone : (Studi Kasus Pada PT. J Ekstrim Tech Indonesia) - Tyas Azmi Noviandini (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine the effect of cost prevention and simultaneously and also appraisal cost of defective products in PT. J Ekstrim Tech Indonesia Cikarang Bekasi. The research method used is quantitative approach with case study method. The data used are primary data and secondary data. The sampling technique used was purposive sampling and samples were taken for 36 months, in the period of January 2012 – December 2020. The data analytical tool in this study is multiple regression equation using the SPSS version 24 application. The result shows that the cost of prevention and appraisal simultaneously have a significant effect on defective products in PT. J Ekstrim Tech Indonesia Cikarang Bekasi simultaneously. Partially cost of prevention has a negative effect while cost of assessment has a positive effect significantly on defective products in PT. J Ekstrim Tech Indonesia Cikarang Bekasi. Partially the cost of appraisal has a negative and unsignificant effect on defective products in PT. J Ekstrim Tech Indonesia Cikarang Bekasi.